Teachers' perspectives of sexual and reproductive health education in primary and secondary schools: a systematic review of qualitative studies. Issue 6 (2nd November 2021) - Walker, Ruth; Drakeley, Sheila; Welch, Rosie; Leahy, Deana; Boyle, Jaqueline
ABSTRACT: School-based sexual and reproductive health (SRH) education is often reported as being inadequate and/or inconsistent. The aims of this systematic review were to synthesise teachers' perspectives on providing SRH education and their opinions about the support required to provide high-quality SRH education in primary and secondary schools. Seven international databases were searched for qualitative studies published since 2010 that reported on teachers' experiences providing SRH education in such settings. Of the 2478 studies identified, 17 met the inclusion criteria. Study quality was assessed using the Mixed-Methods Appraisal Tool. Meta-ethnography was used for data analyses and syntheses. Findings signal how SRH education varied within and between schools. The adequacy of SRH education was linked to i) teachers' confidence to provide such education, ii) school policies and environment, and iii) the priority given to SRH education. Within each of these themes were facilitators or barriers to the provision of good quality SRH education. Facilitators positively impacting on school-based SRH education included training (pre-service and in-service) for all teachers, supportive school environments, and the promotion of understanding of the importance of SRH within schools and in the broader context.